PROBLEMS OF TRAINING SURDOPEDAGOGUES - Makhmudova Oygul Tokhirjonovna (Web of Journals Publishing, 2025)
At the present stage of societal development, in the context of updating the content and methods of education, it is becoming clear that significant changes are needed in the university training of teachers, including defectologists. This is based on developing a new pedagogical paradigm founded on principles of humanism and democracy, and recognizing children's right to education in accordance with modern requirements and individual characteristics.
Keywords: Surdopedagogy, speech, sign language, deaf people, child psychology, defectology